Breaking new ground in pulmonary fibrosis: Targeting Pathways and Therapeutic Innovations - Swadip Mishra (The Journal of Association of Chest Physicians)
Pulmonary fibrosis (PF), particularly idiopathic pulmonary fibrosis (IPF), is a progressive interstitial lung disease characterized by excessive deposition of extracellular matrix components, leading to irreversible scarring and decline in lung function. Despite advances in understanding its pathogenesis, effective treatments remain limited. This review provides a comprehensive analysis of recent discoveries in the molecular mechanisms underlying pulmonary fibrosis, highlighting novel therapeutic targets and emerging treatment strategies that hold promise for improving patient outcomes.